The Influence of CEOs’ Hubris on Firms’ Performance in Indonesia: The Moderating Effects of CEOs’ Power and Board Vigilance - Noni Ayu Rizka; T. Hani Handoko (Gadjah Mada International Journal of Business, 2020)
Past studies on CEO hubris has found that board vigilance is effective in managing the negative outcome of hubris. Some studies found CEO non-duality and independent director representation are effective in decreasing the damage of hubris. However, these studies have only explored the causal relationship of hubris and firm performance in the one-tier corporate governance setting. This study analyzed the influence of CEO hubris on firm performance in Indonesia by taking into account the CEO-board power dynamics. Indonesia adopts the two-tier corporate system where the board is divided into the board of directors and commissioners. Through 99 public listed companies, this study found that hubris in Indonesian CEOs contributes well to firm performance. Moreover, a bigger commissioner board is effective in strengthening the positive influence of hubris on firm performance in Indonesia. Furthermore, this study hints that two-tier corporate governance is more efficient in controlling hubris than the one-tier system.